Electric Energy Substitution Planning for the “14th Five-Year Plan” Period Based on Characteristics of Energy Consumption Structure of Subdivided Industries - Wei TANG; Zhao XU; Baoguo SHAN; Yu ZHANG; Peng WU; Yuelong JIA; Chuncheng ZHANG; Qingkun TAN (Zhongguo dianli)
The implementation of "electric energy substitution" strategy has pushed forward the transformation of energy development mode and will play a crucial role in the future high-quality development of China's energy sector. Firstly, we investigate the existing situation of China's terminal energy consumption and energy supply and the development status quo of electric energy substitution. On this basis, a theoretical potential calculation model of electric energy substitution is proposed based on the characteristics of industrial energy consumption. Secondly, considering the policy, technology and other factors in the planning period, a calculation method of electric energy substitution potential is designed for the“14th Five-Year Plan”period. Thirdly, based on the potential calculation, a planning method of electric energy substitution is proposed for the“14th Five-Year Plan”period. Finally, the development prospect of electric energy substitution is forecasted. Based on the proposed model and methods, it is predicted that the electric energy substitution potential in the operation area of State Grid will exceed 100 billion kW·h, and the planned electric energy substitution will be around 500 billion kW·h during the“14th Five-Year Plan”period. This study can provide a theoretical support for government departments to formulate relevant policies and for the power grid enterprises to implement alternative energy work.